As poéticas contemporâneas e o ensino da Arte: por um pensamento ambiental/sustentável - OLIVEIRA, Maria Risolange Tavares de (2020)
This quantitative-qualitative research of an artistic / pedagogical nature aims to analyze a creative process to understand the reuse of discarded materials and objects as a means of encouraging and contributing to the awakening of an artistic and environmental / sustainable awareness of 9th grade students. Gomes de Sousa Basic Unit. The school institution participating in this research is located in the rural area of São Luís, a region in which the population lives the following dichotomy: on the one hand, the social, economic and cultural deficiencies and ailments and on the other the large companies that set up in the locality, devastating, deforesting and polluting their mangroves and seas, transporting the wealth of Maranhão through the Port of Itaqui to other countries and states. We set out to investigate the educational action in the use of solid waste in the creative process, leading students to recognize in these resources artistic possibilities, building a sense of awareness in relation to care for sustainability and the environment. We used Contemporary Art, from the study of the work of the artists Frans Krajcberg, Vik Muniz and Claudio Costa as a form of expression for social and educational inclusion and recognition, showing the possibility of reuse and reframing used by them in their work. The research is based on bibliographical authors such as: Guattari (2017), Gullar (2005), Certeau, (2018) and Dewey (2010). The research showed through questionnaires applied to the families of the participating students that they, through studies and practical activities carried out during the project, presented changes in the way they deal with the waste discarded in their day-to-day lives, being noticeable the awakening of artistic, environmental and sustainable awareness from the artistic and educational possibilities of reusing materials and objects discarded in nature, understanding that it is possible to produce art while preserving the environment.